2009
DOI: 10.1371/journal.pone.0004631
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Paraptosis Induction: Implications for a Non-Genetically Modified Tumor Vaccine

Abstract: Paraptosis is the programmed cell death pathway that leads to cellular necrosis. Previously, rodent and human monocytes/macrophages killed glioma cells bearing the membrane macrophage colony stimulating factor (mM-CSF) through paraptosis, but the molecular mechanism of this killing process was never identified. We have demonstrated that paraptosis of rat T9 glioma cells can be initiated through a large potassium channel (BK)-dependent process initiated by reactive oxygen species. Macrophage mediated cytotoxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
48
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 43 publications
3
48
0
Order By: Relevance
“…[14] It is characterized by cytoplasmic reorganization, enlargement of the endoplasmic reticulum and mitochondria, swelling of the cell and formation of extensive cytoplasmic vacuoles. [15] In the eye, paraptosis has been portrayed in retinal ganglion cells following glaucoma induced retinal ischemia/reperfusion injury, a major cause of vision loss in the human. [16,17] In addition, paraptosis in the corneal epithelium may occur in pathological conditions such as corneal dystrophies.…”
Section: Discussionmentioning
confidence: 99%
“…[14] It is characterized by cytoplasmic reorganization, enlargement of the endoplasmic reticulum and mitochondria, swelling of the cell and formation of extensive cytoplasmic vacuoles. [15] In the eye, paraptosis has been portrayed in retinal ganglion cells following glaucoma induced retinal ischemia/reperfusion injury, a major cause of vision loss in the human. [16,17] In addition, paraptosis in the corneal epithelium may occur in pathological conditions such as corneal dystrophies.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, we showed that prolonged activation of BK channels of T9 or U251 gliomas in vitro causes cell swelling and eventually leads to paraptosis (7,8). When paraptotic BK channel-activated/killed T9 cells were used as the immunogen, T9-specific tumor immunity toward the T9 glioma cells was generated within naive rats (8). BK channel activators were created and successfully prevented cardiac reperfusion injury in animals (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Both chloride channel-1 and aquaporins are also overexpressed in glioma (41)(42)(43). BK channel activation leads to cell swelling, whereas CLIC1 activation leads to cell shrinkage (7,8,44). Both of these functions, swelling and shrinking, are needed for cell volume regulation and motility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations